Development and pilot implementation of a standardised trauma documentation form to inform a national trauma registry in a low-resource setting: lessons from Tanzania. Issue 10 (8th October 2020) - Sawe, Hendry R; Reynolds, Teri A; Weber, Ellen J; Mfinanga, Juma A; Coats, Timothy J; Wallis, Lee A
Abstract : Objectives: Trauma registries are an integral part of a well-organised trauma system. Tanzania, like many low and middle-income countries, does not have a trauma registry. We describe the development, structure, implementation and impact of a context appropriate standardised trauma form based on the adaptation of the WHO Data Set for Injury (DSI), for clinical documentation and use in a national trauma registry. Setting: Our study was conducted in emergency units of five regional referral hospitals in Tanzania. Procedures: Mixed methods participatory action research was employed. After an assessment of baseline trauma documentation, we conducted semi-structured interviews with a purposefully selected sample of 33 healthcare providers from all participating hospitals to understand, develop, pilot and implement a standardised trauma form. We compared the number and types of variables captured before and after the form was implemented. Outcomes: Change in proportion of variables of DSI captured after implementation of a standardised trauma documentation form. Results: Piloting and feedback informed the development of a context appropriate standardised trauma documentation paper form with carbonless copy that could be used as both the clinical chart and data capture. Among 721 patients (seen by 21 clinicians) during the initial 30-day pilot, overall variable capture was 86.4% of required variables. After modifications of the form and training of healthcare providers, the form was implemented for 7 months, during which the capture improved to 96.3% among 6302 patients (seen by 31 clinicians). The providers reported the form was user-friendly, resulted in less time documenting, and served as a guide to managing trauma patients. Conclusions: The development and implementation of a contextually appropriate, standardised trauma form were successful, yielding increased capture rates of injury variables. This system will facilitate expansion of the trauma registry across the country and inform similar initiatives in Sub-Saharan Africa.